Using NS1 flavivirus protein microarray to infer past infecting dengue virus serotype and number of past dengue virus infections in Vietnamese individuals - Thao, TTN; de Bruin, E; Phuong, HT; Thao Vy, NH; van den Ham, H-J; Wills, BA; Tien, NHT; Le Duyen, HT; Trung, DT; Whitehead, SS; Boni, MF; Koopmans, M; et al. (Oxford University Press, 2020)
Background In recent years, researchers have had an increased focus on multiplex microarray assays, in which antibodies are measured against multiple related antigens, for use in seroepidemiological studies to infer past transmission.